EU-Japan Agreement on Mutual Legal Assistance in Criminal Matters - Redaktion, Die (Zeitschrift für Japanisches Recht, 2011)
The European Union and Japan have concluded an Agreement providing for mutual legal assistance in criminal matters between Japan and the twenty-seven EU Member States. It went into force on 2 January 2011; its official languages are English and Japanese. Hereafter, we present to our readers both a press release of the Council of the European Union of 18 October 2010 (A) and the main text of the Agreement (B; the three appendices are not reprinted), which was published in English language in the Official Journal of the European Union, 12.2.2010, L 39/20-35. (The Editors)